Revisiting the Role of Corporate Governance: Evidence on R&D, Marketing Intensity, and Profitability in Indonesian Pharmaceutical Firms - Ida Ayu Surasmi; Made Setini (International Journal of Applied Business and International Management, 2026)
Firm profitability is a critical indicator of business sustainability, particularly in competitive industries such as pharmaceutical manufacturing, where innovation, marketing, and governance play essential roles. This study examines the effect of research and development (RD) expenditure and marketing intensity on firm profitability, with corporate governance as both an independent and moderating variable. Using panel data from pharmaceutical firms listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period, this study applies Moderated Regression Analysis (MRA). The results show that RD expenditure (? = 3.392; p 0.001) and marketing intensity (? = 0.393; p = 0.015) have a significant positive effect on profitability (ROA), while corporate governance also has a significant positive direct effect (? = 2.114; p 0.001). However, the interaction effects are not significant, indicating that corporate governance does not moderate these relationships. The model is statistically significant (F = 14.662; p 0.001) with moderate explanatory power (R² = 0.604). These findings highlight the importance of strategic investment in innovation, marketing, and governance. This study contributes to the literature by positioning corporate governance as an independent determinant rather than a moderating mechanism and provides practical implications for improving firm performance.